PELATIHAN MANAJEMEN DAN PELAKSANAAN K3 PENGELASAN UNTUK MASYARAKAT PELAKU USAHA PENGELASAN DI DESA PAYAKABUNG: TRAINING IN WELDING OCCUPATIONAL HEALTH AND SAFETY (OHS) MANAGEMENT AND IMPLEMENTATION FOR WELDING ENTERPRISE PRACTITIONERS IN PAYAKABUNG VILLAGE - Anugerah Agung Ramadhan; Harlin; Farhan Yadi; Yogi herdianto; Romy Saputra; Efri Meldianto (LPPM Universitas Abdurrab, 2026)
This Community Service Program (PkM) aims to address three major gaps across six micro welding businesses in Payakabung Village, namely behavioral gaps (low PPE awareness), knowledge gaps (weak basic OHS management), and access gaps (limited availability of quality PPE). This activity involved 15 participants consisting of business owners and welding workers. The problem solving strategy is divided into two activities: Human Resource Capacity Building and the Implementation of Renewable Technology Interventions. Evaluation results indicate significant program effectiveness. Based on pre-test and post-test instruments, there was an increase in the average OHS knowledge score by 43.3 points, with the training effectiveness reaching 95.8% (from an average pre-test score of 45.2 to a post-test score of 88.5). Qualitatively, improvements were observed in PPE compliance and welding OHS implementation. This program contributes to achieving SDG 8 (Decent Work), SDG 3 (Good Health and Well-being), and SDG 4 (Quality Education), and supports the vision of Universitas Sriwijaya (UNSRI) in developing highly competitive human resources